SPSS for research methods : a basic guide - Wilson-Doenges, Georjeanna (New York: W.W Norton & company, 2022)
"This is a guide showing the best ways for students to analyze data and interpret results in SPSS. Georjeanna Wilson-Doenges's direct writing style, real sample data from her research methods class, integrated APA-style results, and detailed yet clear screenshots ensure students will be confident and enthusiastic about using SPSS. The second edition reflects the latest APA guidelines and SPSS interface upgrade"--
Includes bibliographical references and index.
Keywords: SPSS for Windows; Social sciences -- Research -- Methodology; Social sciences -- Statistical methods -- Computer programs